Synthesis of MoS2/YVO4 composite and its high photocatalytic performance in methyl orange degradation and H2 evolution. (1st September 2018) - Chen, Qianqian; Zhao, Chunran; Wang, Yan; Chen, Yijing; Ma, Yueyin; Chen, Zhiqiang; Yu, Jingxiong; Wu, Ying; He, Yiming
Highlights: MoS2 /YVO4 composite was prepared by a hydrothermal method. MoS2 /YVO4 showed high efficiency in photocatalytic H2 generation and MO degradation. The H2 generation rate of MoS2 /YVO4 is 11.3 times faster than that of YVO4 . The MO degradation rate constant of MoS2 /YVO4 is 4.4 times higher than that of YVO4 . The influence factors on the photoactivity of MoS2 /YVO4 were investigated. Abstract: This work was designed to ameliorate the photocatalytic performance of YVO4 by using MoS2 as a co-catalyst. MoS2 was in-situ decorated on the surface of YVO4 nanoparticles through a simple hydrothermal process. The synthesized MoS2 /YVO4 composite was characterized by various techniques, including XRD, Raman, XPS, SEM, TEM, DRS, PL, EIS and PC. Results indicate that MoS2 acts as an electron trapper in the binary system, which hinders the recombination of charge carriers and enhances the utilization of the photogenerated charge carriers in the photocatalytic reaction. Therefore, MoS2 /YVO4 composite presents high activity in the photocatalytic degradation of methyl orange (MO) and the generation of H2 under simulated sunlight irradiation. 2.5% MoS2 /YVO4 sample has the best performance in H2 generation with a H2 -evolution rate of 134 μmol g −1  h −1, which is 11.2 times higher than that of pure YVO4 . For photocatalytic degradation of MO, 10%MoS2 /YVO4 shows the best efficiency. The degradation rate constant is 4.4 times larger than that of pure YVO4 . The different optimal content of MoS2 can be ascribed to that the two reactions are performed in different ways. This work may provide some valuable information for the future design of high efficient photocatalysts by using MoS2 as a co-catalyst.